Accumulation of Stimulants of Toll-Like Receptor (TLR)-2 and TLR4 in Meat Products Stored at 5 °C - Erridge, Clett (Journal of food science, 2011)
:  Recent evidence suggests that exposure to stimulants of the innate immune receptors Toll‐like receptor (TLR)‐2 and TLR4 may contribute to the development of atherosclerosis and insulin resistance. We showed recently that common foodsuffs can contain TLR‐stimulants, and that the greatest concentrations were present in meat‐based products. Using a recently developed quantitative bioassay, we here examined the kinetics of accumulation of TLR2‐ and TLR4‐stimulants in a variety of meat products held at 5 °C in air or under a modified atmosphere for up to 8 d. Meat content of TLR‐stimulants increased with time in each meat examined and was paralleled by growth of pseudomonads and Enterobacteriaceae, suggesting that bacterial lipopeptides and lipopolysaccharides are the likely sources of TLR2‐ and TLR4‐stimulants, respectively. TLR‐stimulants reached the highest levels (approximately 80 μg lipopeptide‐equivalents per gramme and approximately 7 μg lipopolysaccharide‐equivalents per gram) in meat that was minced rather than intact, and when stored in air rather than under a modified atmosphere. TLR2‐ and TLR4‐stimulants in meat products cooked for 1 h retained approximately 20% and approximately 40% of their bioactivity, respectively. In summary, storage conditions and microbial flora critically regulate the kinetics of TLR2‐ and TLR4‐stimulant accumulation in meat products and these may retain biological activity after cooking. Practical Application:  The novel assays presented in this work could be used to predict the potential of foodstuffs to promote inflammatory signaling in human subjects, which may be deleterious to health. These assays may also be used to monitor the historical microbial flora in food products after cooking or other forms of food processing may have rendered the original microflora nonviable.